UNCONVENTIONAL WOUND-HEALING STRATEGIES: A NARRATIVE REVIEW OF THE LITERATURE, EMPHASIZING AESTHETIC MEDICINE MODALITIES - Mikołaj Herba; Sylwia Boczek; Kacper Ordon; Patrycja Misiaszek; Maciej Karwat (International Journal of Innovative Technologies in Social Science, 2025)
Background. In 2019, the United States devoted 126 billion to wound care—constituting 16.3 % of all patient-borne healthcare expenditures—an increase from 14.5 % in 2014, representing a 1.8-percentage-point rise. In Poland, expenditures on wound management reached 1.45 billion in the same year, accounting for 5.6 % of the national healthcare budget. These figures underscore wound care as a critical, interdisciplinary challenge for healthcare systems worldwide. Aim. Synthesize current approaches to wound management and to elucidate the adjunctive potential of aesthetic medicine techniques in promoting tissue regeneration. Material and methods. Between April and June 2025, we conducted a comprehensive literature search of PubMed, PMC and Google Scholar using the following keywords: “aesthetic medicine,” “wound healing,” “chronic wounds,” “mesotherapy,” “laser therapy,” and “stem cells in aesthetic medicine.”. Results. Mesotherapy enhanced burn closure in rat models (glutathione reduced residual wounds to 22.7 cm² versus 46.4 cm² controls). Laser therapies (CO₂, Er:YAG, fractional) improved hypertrophic scar remodeling and chronic wound re‐epithelialization, reduced inflammation, and increased collagen and angiogenesis. Microneedling and ASC-based mesotherapy accelerated hypertrophic and venous ulcer healing metrics. Conclusions. The studies cited above have demonstrated that procedures employed in aesthetic medicine may offer significant benefits as an adjuvant therapy in the wound-healing process. In particular, emphasis has been placed on the use of high-energy sources—namely, lasers—which markedly enhance the healing of chronic wounds, especially in patients burdened by multiple comorbidities.